1985
DOI: 10.1073/pnas.82.19.6586
|View full text |Cite
|
Sign up to set email alerts
|

Growing Xenopus oocytes have spare translational capacity.

Abstract: Previous studies have shown that exogenous mRNAs injected into full-grown (stage 6) Xenopus oocytes are translated only at the expense of endogenous messages; translational capacity is limited. In this report, we demonstrate that injection of globin mRNA into small, stage 4 oocytes results in an increase in total protein synthesis without a concomitant decrease in the translation of endogenous mRNAs. The absence of competition with endogenous messages in stage 4 oocytes injected with globin mRNA, compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…A review where more than 200 références to papers dealing with mRNA translation in Xenopus oocytes can be found has been recently published by Soreq (1985). Injection of globin mRNA into young, vitellogenic oocytes is also followed by globin expression; in such oocytes, in contrast to full-grown oocytes, there is no compétition between foreign and endogenous mRNAs for the protein-synthesizing machinery (Taylor et al, 1985).…”
Section: Oogenesismentioning
confidence: 99%
“…A review where more than 200 références to papers dealing with mRNA translation in Xenopus oocytes can be found has been recently published by Soreq (1985). Injection of globin mRNA into young, vitellogenic oocytes is also followed by globin expression; in such oocytes, in contrast to full-grown oocytes, there is no compétition between foreign and endogenous mRNAs for the protein-synthesizing machinery (Taylor et al, 1985).…”
Section: Oogenesismentioning
confidence: 99%
“…Therefore, oocyte stockpiles huge amounts of biological material (protein, RNA, lipids) for later usage. Even though, oocyte is quite active in protein synthesis during development, it has been reported that only a portion of the ribosome is active and they are stored for later use (Taylor et al, 1985). Metabolic pathway members, particularly, glycolysis members might be needed to contribute energy requirement of the giant oocyte during oogenesis and later during embryogenesis.…”
Section: Quantitative Proteome Analysis Of X Laevis Oocytementioning
confidence: 99%